2016
DOI: 10.1111/jomf.12352
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress, Couple Interactions, and Parenting: A Dyadic Analysis of African American Couples

Abstract: Parental depression is a well‐established risk factor for couple conflict and ineffective or hostile parenting (M. C. Lovejoy, P. A. Graczyk, E. O'Hare, & G. Neuman, 2000; L. M. Papp, M. C. Goeke‐Morey, & E. M. Cummings, 2007). Although research suggests that caregiver depression may impact parenting indirectly via increased conflict between couples (e.g., R. D. Conger et al., 2002), few studies take into account the behaviors of both caregivers in exploring these relations. The goal of the current study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 70 publications
4
30
1
Order By: Relevance
“…As there are no previous studies supporting the effect of maternal psychological distress on the relationship between paternal psychological distress and fathers’ involvement in childcare, an accurate comparison of the present results with previous research is difficult; however, maternal psychological distress has been reported to influence fathers’ involvement in childcare [31]. It is thus very important to reduce maternal psychological distress to guarantee the quality and quantity of fathers’ involvement in childcare.…”
Section: Discussionmentioning
confidence: 57%
“…As there are no previous studies supporting the effect of maternal psychological distress on the relationship between paternal psychological distress and fathers’ involvement in childcare, an accurate comparison of the present results with previous research is difficult; however, maternal psychological distress has been reported to influence fathers’ involvement in childcare [31]. It is thus very important to reduce maternal psychological distress to guarantee the quality and quantity of fathers’ involvement in childcare.…”
Section: Discussionmentioning
confidence: 57%
“…Apart from the focus on samples from high‐income countries, another limitation in this research area is that few studies have used a dyadic approach in examining the relation between parent psychological health and parenting (Sutton, Simons, Simons, & Cutrona, 2017). From a family systems perspective, the quality of the marital relationship is interrelated with the quality of the parent–child relationship (Engfer, 1988; Erel & Burman, 1995).…”
Section: Depressive Symptoms and Parentingmentioning
confidence: 99%
“…Specifically, parent gender may also moderate the spillover effect and crossover effect between interparental conflict and parental emotion socialization. Previous research (e.g., Sutton et al, 2017) utilizing the father vulnerability hypothesis (e.g., Cummings, Goeke-Morey, & Raymond, 2004; Davies, Sturge-Apple, Woitach, & Cummings, 2009), for example, shows that fathers’ parenting is more vulnerable to destructive interparental conflict than mothers’ parenting. There are several possible explanations for this greater vulnerability.…”
Section: Dyadic Relations Between Mothers and Fathersmentioning
confidence: 99%
“…Thus, mothers who experience greater conflict may model ineffective strategies for managing emotion. Recently, Sutton, Simons, Simons, and Cutrona (2017) found that fathers as well as mothers who had few skills to interact in warm and supportive ways with their partner showed less warm and more hostile behaviors to their children. These researchers specifically suggested that stress of negative interparental interactions may spill over into parent-child interactions.…”
Section: Interparental Conflict and Parental Emotion Socializationmentioning
confidence: 99%